Picosecond-resolution soft-x-ray laser plasma interferometry - Shlyaptsev, Vyacheslav N., author; Ng, Andrew, author; Nilsen, Joseph, author; Moon, Stephen J., author; Hunter, James R., author; Keenan, Roisin, author; Dunn, James, author; Smith, Raymond F., author; Marconi, Mario C., author; Rocca, Jorge J., author; Filevich, Jorge, author; Optical Society of America, publisher (Colorado State University. Libraries, 2004)
We describe a soft-x-ray laser interferometry technique that allows two-dimensional diagnosis of plasma electron density with picosecond time resolution. It consists of the combination of a robust high-throughput amplitude-division interferometer and a 14.7-nm transient-inversion soft-x-ray laser that produces ~5-ps pulses. Because of its picosecond resolution and short-wavelength scalability, this technique has the potential for extending the high inherent precision of soft-x-ray laser interferometry to the study of very dense plasmas of significant fundamental and practical interest, such as those investigated for inertial confinement fusion. Results of its use in the diagnostics of dense large-scale laser created plasmas are presented.